Perceptions of Urban Farming Actors on Hydroponic-Based Agricultural Development within Urban Agrifood Systems - Bakri, Muhammad Yusuf; Nurhapsa; Wahyuningsih, Andi Erna Sri (Edupedia Publisher, 2025)
Urban farming is increasingly promoted as an adaptive response to food system challenges in rapidly urbanizing areas. This study analyzes the perceptions of urban farming actors toward hydroponic-based agricultural development within urban agrifood systems. A census-based survey was conducted among hydroponic practitioners participating in an urban farming program in Parepare City, Indonesia. Data were collected using a structured Likert-scale questionnaire and analyzed descriptively to capture technical, economic, institutional, and market-related perception dimensions. The results show that hydroponic urban farming is perceived as technically feasible and well-suited to limited urban spaces, with positive contributions to household food provision. However, perceptions of income potential, market integration, and program continuity remain moderate, indicating structural constraints that limit wider agrifood system impacts. These findings suggest that hydroponic urban farming currently functions mainly as a complementary food production strategy rather than a fully commercial activity. The study highlights that long-term sustainability depends not only on technological adoption but also on sustained institutional support and stronger integration with urban food markets, emphasizing the need for system-oriented development approaches.